Does economic policy uncertainty impact inflation? - Moldovan, P.; Lagoa, S.; Mendes, D. (MIRDEC 18th International Academic Conference Economics, Business and Contemporary Discussions in Social Science: Conference Proceedings, 2022)
Using the monthly economic policy uncertainty (EPU) index of Baker et al. (2016), we examine its impact on inflation rate in the UK over the period from 1998 to 2020. We adopt a vector autoregressive (VAR) model and generate impulse response functions. To ensure that the identified shocks will be uncorrelated, based on economic theoretical considerations, we employed Cholesky restrictions. The results show that a positive innovation in EPU index leads to a weakening of the real exchange rate and unemployment rate and at the same time a rise in inflation rate. The broad implication of the present research is that under economic policy uncertainty shocks, inflation and unemployment rate respond in accordance with the effects described by the economic theory and the Phillips curve, which emphasizes that there is a trade-off between inflation and unemployment.